Cyclosporin A in the treatment of chronic demyelinating polyradiculoneuropathy. - Hodgkinson, S J (1990)
Eight patients with chronic inflammatory demyelinating polyneuropathy, five of whom had an associated paraproteinaemia, were treated with cyclosporin in a pilot, uncontrolled study for periods up to three and a half years after failing to respond adequately to corticosteroid and azathioprine therapy and plasmapheresis. Three patients had an excellent response, two with complete remission. In other cases it was possible to reduce the corticosteroid therapy and frequency of plasmapheresis. There were no serious complications of the treatment.